A glycopore for bacterial sensing - Shanley, SJ (2009)
Increasing antibiotic resistance has created a need to develop rapid and reliable methods to identify bacteria and provide pertinent information to ensure suitable antibiotics or sugar therapeutics can be chosen for treatment. Carbohydrate structures attached to proteins on host cell surfaces provide a binding point for many pathogens, including bacteria. These structures can be mimicked using single monosaccharides glycosylated to alpha-hemolysin (alpha-HL). Alpha-HL is a beta-barrel pore-forming toxin secreted by Staphylococcus aureus that forms an SDS stable heptamer, which can be expressed by coupled in vitro transcription and translation and purified by polyacrylamide gel electrophoresis. The purified heptamers can be reconstituted into planar lipid bilayers and studied at the single channel level. Through single channel recordings the effects of sugar-linker lengths, different glycans and the interaction between the ‘Glycopore’ and sugar binding molecules can be studied. The glycopore, therefore, acts as a scaffold for analysing protein-sugar interactions. Studies in this thesis have focused on the synthesis of carbohydrates for site-selective protein glycosylation; cloning and in vitro transcription translation of alpha-HL monomers; and glycosylation and oligomerisation of alpha-HL to form glycopores suitable for lectin-binding studies. Lectins DC-SIGN and FimH have been expressed in Escherichia coli and these lectins as well as others have been screened using alpha-HL glycopores. The glycopores have also been investigated with bacteria in serum in a controlled molecule-specific manner using single-channel electrical recording. In this work glycosylated alpha-HL-monomers have been found to form stable heptamers which can be formed by oligomerisation on red blood cell membranes. The purified glycopores were reconstituted into planar lipid bilayers and studied at the single-channel level. Through single-channel recordings an optimised glycopore has been shown to be effective in distinguishing lectins alone and in a mixture and has afforded qualitative and quantitative information about the binding interactions between carbohydrates and sugar binding proteins. Furthermore, the glycopore has been used to sense bacteria which may provide an insight into modes of bacterial infection. In addition, a multivalent glycopore has been formed which has proved preliminary information about the effects of multivalency in lectin binding. The design and synthesis of non-beta-lactam antibiotic candidates and their evaluation has also been carried out.